Clinical management of a rare Peters’ anomaly-induced secondary childhood glaucoma: A case report - Imelda, Eva; Gunawan, Fany (Narra Sains Indonesia, 2021)
Childhood glaucoma is a rare disorder that occurs from birth until teenage years caused by an abnormality of aqueous humor pathways. About 50–70% of Peters' anomaly is accompanied by secondary childhood glaucoma. The presence of glaucoma will affect the prognosis. We reported the evaluation and treatment of secondary childhood glaucoma due to Peters’ anomaly. A 5 months-old boy was presented with the complaint of a enlarged left eye since 3 months old. The complaint was accompanied by a watering eye and frequently closed upon light exposure. The left eye looked opaquer than contralateral. Examination under anesthesia showed that the intraocular pressure (IOP) was 35 mmHg in the left eye and the corneal diameter was 14 mm. Other findings were keratopathy, diffuse corneal edema, buphthalmos, shallow anterior chamber, anterior synechiae, and linear slit shaped pupils in the nasal region. Patient was treated with ophthalmic timolol maleate which was later followed by trabeculectomy. After 1 week post-surgery, IOP assessment by palpation suggested the right eye within normal range while the IOP of left eye was higger than normal. Blepharospasm, epiphora, photophobia, bleb on superior, subconjunctiva bleeding, buphthalmos, keratopathy, minimal corneal edema, anterior chamber with shallow image, and posterior synechia were found in left eye anterior segment. In conclusion, trabeculotomy and trabeculectomy are recommended if there is no reduction of IOP observed after receiving timolol maleate therapy. The choice of surgical management is dependent on the feasibility of the protocol.